Anti-CD20 versus Dimethyl Fumarate as First-Line Treatment for Pediatric Multiple Sclerosis: A Retrospective Cohort Study - Etemadifar, Masoud; Ramezani, Aryana; Miralaei, Pantea; Sedaghat, Nahad; Jozaie, Amir M.; Ghorbani, Mehrzad; Salari, Mehri; Kaveyee, Hasan (Neuropediatrics, 2025)
Consensus on the first-line treatment of pediatric-onset multiple sclerosis (POMS) remains unresolved. Recently, dimethyl fumarate (DMF) and anti-CD20 therapies have been among the favorable options for pediatric multiple sclerosis (MS).This study aimed to determine the effectiveness and safety of DMF versus anti-CD20 therapies for POMS.We conducted a retrospective cohort study from July 2012 to July 2022 in the Isfahan MS clinic. MS cases under the age of 18 years old who received DMF or anti-CD20 agents as first-line treatment and were followed for at least 12 months were included.About 124 POMS cases were screened, of which 39 met the inclusion criteria. About 23 patients received DMF, while 16 patients received anti-CD20 (rituximab or ocrelizumab). The median (interquartile range, IQR) annualized relapse rate (ARR) decreased significantly (both with p < 0.0001) from 2.63 (0.68) to 0.0 (1.0) in the DMF group and from 2.89 (1.39) to 0.0 (1.0) in the anti-CD20 group. The median (IQR) expanded disability status score insignificantly changed from 1.0 (1.0) to 1.0 (0.5) in the DMF group, while it changed from 1.25 (1.0) to 1.0 (0.5) in the anti-CD20 group. After 12 months of follow-up, 12/16 in the anti-CD20 group and 17/23 in the DMF group were relapse-free. None of the treatment outcomes were different between the two treatment cohorts. Our study also assessed adverse events (AEs).While subject to replication in future clinical trials, both DMF and anti-CD20 therapies had a significant effect on reducing ARR and disease activity with an acceptable safety profile, but in our study, there were no differences in their efficacy.
Keywords: pediatric-onset multiple sclerosis; anti-CD20; dimethyl fumarate; rituximab; ocrelizumab; disease-modifying treatment